DIREKTORI DATA PESANTREN DI KABUPATEN MALANG (Profiling dan Pengembangan Direktori Pesantren Center) - Abdurrahman (Pascasarjana Institut Agama Islam Al-Qolam, 2022)
Pesantren is a non formal educational institution that is one of the important means in the spread of Islam in Indonesia. The existence of pesantren for the lives of Indonesian people has a very significant role. Therefore, the study of pesantren, especially those related to the collection of pesantren, becomes important to do. Meanwhile, in the statistical report of Malang regency, the number of pesantren in Malang regency in 2019 amounted to 724 pesantren in 33 sub-districts. The data according to the study while some RMI PC managers are data that also cannot be valid values, because it is likely that many enter institutions other than pesantren, such as TPQ, Majlis Ta'lim or Madrasah Diniyah. Thus, this research project becomes very important to provide serious assistance to the creation, development and development of pesantren directories on the pesantren center website, the implementation of pesantren data collection through pesantren profiling programs, and ensuring the entry of pesantren profiling data into the directory system. The creation and development of the pesantren directory system on the Pesantren Center website can be carried out properly and in accordance with the planned targets. Even this system product exceeds the expectations of some members of pesantren center itself who can produce web-based application products with a coding system that is quite user friendly very easy to use by teams, officers and program agent profiling. Keywords: Data Directory, Profiling, Pesantren